Analysis of volatile flavor compounds in top fermented wheat beer by headspace sampling-gas chromatography - Li, Huimin; Li, Hongjun; Liu, Xiuhua; Chen, Bing (International Journal of Agricultural and Biological Engineering, 2012)
Li Huimin, Li Hongjun*, Liu Xiuhua, Chen Bing(School of Agriculture and Food Engineering, Shandong University of Technology, Zibo 255049, China)Abstract: Headspace sampling-gas chromatography (HS-GC) coupled with an internal standard method (ISM) was developed to analyze the volatile flavor compounds in top fermented wheat beer in the laboratory. Eight compounds, i.e. acetaldehyde, N-propanol, ethyl acetate, isobutyl alcohol, isoamyl alcohol, isoamyl acetate, ethyl hexanoate and ethyl octanoate were separated and quantified. This method was validated to ensure the quality of the results: the precision was satisfactory with relative standard deviation (RSD) in the range of 1.51%-4.22%, recoveries for all the analytes ranged from 95.15% to 99.85%, and the limits of detection were in the range of 0.0002-0.024 mg/L. Results of real wheat beer samples analyzed using this method showed that the volatile compound concentrations were in the range of 0.08-99.91 mg/L. Results suggested that this method exhibited good reproducibility, selectivity and high precision, and it can be useful for the analysis of routine beer samples.Keywords: top fermentation, wheat beer, flavor detection, volatile flavor compounds, headspace sampling-gas chromatography, internal standard methodDOI: 10.3965/j.ijabe.20120502.009Citation: Li H M, Li H J, Liu X H, Chen B. Analysis of volatile flavor compounds in top fermented wheat beer by headspace sampling-gas chromatography. Int J Agric & Biol Eng, 2012; 5(2): 67